2023
DOI: 10.3390/membranes13020208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Pseudomonas Strain on the Lipid Transfer Proteins, Appoplast Barriers and Activity of Aquaporins Associated with Hydraulic Conductance of Pea Plants

Abstract: Lipid transfer proteins (LTPs) are known to be involved in suberin deposition in the Casparian bands of pea roots, thereby reinforcing apoplast barriers. Moreover, the Pseudomonas mandelii IB-Ki14 strain accelerated formation of the Casparian bands in wheat plants, although involvement of LTPs in the process was not studied. Here, we investigated the effects of P. mandelii IB-Ki14 on LTPs, formation of the Casparian bands, hydraulic conductance and activity of aquaporins (AQPs) in pea plants. RT PCR showed a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…In two recent studies, a research group discovered that a Pseudomonas strain known as P. mandelii IB-Ki14 was able to help wheat and pea better tolerate salt in the soil by increasing the deposition of suberin and lignin in xylem cell walls, suberin lamellae, and Casparian strips (Figure 4; Martynenko et al, 2022Martynenko et al, , 2023. These structures are important apoplastic barriers in the root endodermis controlling water and mineral influx into the root stele.…”
Section: A Pseudomonas Strain Strengthens the Root Apoplast Barriers ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent studies, a research group discovered that a Pseudomonas strain known as P. mandelii IB-Ki14 was able to help wheat and pea better tolerate salt in the soil by increasing the deposition of suberin and lignin in xylem cell walls, suberin lamellae, and Casparian strips (Figure 4; Martynenko et al, 2022Martynenko et al, , 2023. These structures are important apoplastic barriers in the root endodermis controlling water and mineral influx into the root stele.…”
Section: A Pseudomonas Strain Strengthens the Root Apoplast Barriers ...mentioning
confidence: 99%
“…Accumulation of abscisic acid in plants, a phytohormone involved in the plant stress response, usually leads to these effects on apoplastic barriers under salt stress conditions (Martynenko et al, 2023). However, the authors showed that there was no such accumulation in pea plants inoculated with P. mandelii IB-Ki14, which led them to suggest that these salt stress-alleviating effects may be ABA-independent (Martynenko et al, 2023). However, P. mandelii IB-Ki14 was able to improve IAA levels in roots, which may mediate the observed effects.…”
Section: A Pseudomonas Strain Strengthens the Root Apoplast Barriers ...mentioning
confidence: 99%
“…To achieve this goal, we used immunohistochemical localization with antibodies to these hormones. The choice of peas was dictated by the fact that we have previously obtained data on the localization of abscisic acid in pea roots [28].…”
Section: Of 13mentioning
confidence: 99%
“…Studies were carried out on a pea (Pisum sativum L.) cultivar, Sakharny 2. Before the start of the experiments, pea seeds were disinfected with a mixture of 96% ethanol and 3% hydrogen peroxide (in a ratio of 3:1) for 10 min as described [28]. Then the seeds were thoroughly washed under running water and left overnight in water to swell under continuously aerated conditions.…”
Section: Plant Growth and Collecting Plant Materialsmentioning
confidence: 99%
“…This problem remained unresolved if the same effect occurred in the absence of salinity, affecting the hydraulic conductivity of plants. Staining with berberine hemisulfate confirmed that bacterial treatments increased the deposition of lignin and suberin and the formation of Casparian bands in roots of barley and pea [ 23 , 24 ]. Calculation of hydraulic conductivity through correlating transpiration to the leaf water potential showed that it did not decrease in plants treated with bacteria.…”
Section: Introductionmentioning
confidence: 99%